The Influence of Transformational Leadership Style and Work Environment on the Performance of State Civil Apparatus Employees with Motivation as an Intervening Variable in the North Sumatra Provincial Youth and Sports Office - Apri Sugiarto; Wilchan Robain; M. Alfahmi (Yayasan Multidimensi Kreatif, 2025)
This study aims to look at the Influence of Transformational Leadership Style and Work Environment on Employee Performance and Civil Service Motivation as an Intervening Variable in the North Sumatra Provincial Youth and Sports Office, Human Resources (HR) are generally productive individuals who work as the driving force of an organization, both in institutions and companies that have a function as an asset so that they must be trained and developed their abilities. Human resources generally consist of two, namely macro human resources, namely the number of people of productive age in a region, and micro human resources in a narrow sense, namely individuals who work for an institution or company. The results of this study are as follows: Transformational Leadership Style has a positive and significant effect on Employee Performance with an original sample value of 0.388 and p values of 0.002. Transformational Leadership Style had a positive and significant effect on Motivation with an original sample value of 0.572 and p values of 0.000. The Work Environment had a positive and insignificant effect on Employee Performance with an original sample value of 0.149 and p values of 0.109. The Work Environment had a positive and significant effect on Motivation with the original sample value of 0.371 and p values of 0.000. Motivation had a positive and significant effect on Employee Performance with an original sample value of 0.396 and p values of 0.001. Transformational Leadership Style has a positive and significant effect on Employee Performance through Motivation with an original sample value of 0.226 and p values of 0.001. The Work Environment has a positive and significant effect on Employee Performance through Motivation with an original sample value of 0.147 and p values of 0.016.